2013
DOI: 10.1111/j.1542-4774.2012.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Labor-Market Heterogeneity, Aggregation, and Policy (In)variance of Dsge Model Parameters

Abstract: Data from a heterogeneous-agents economy with incomplete asset markets and indivisible labor supply are simulated under various fiscal policy regimes and an approximating representative-agent model is estimated. Preference and technology parameter estimates of the representative-agent model are not invariant to policy changes and the bias in the representative-agent model's policy predictions is large compared to predictive intervals that reflect parameter uncertainty. Since it is not always feasible to accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 74 publications
3
35
0
Order By: Relevance
“…The method of approximating the expected utility of households through the weighted average of the variances of selected variables has a long tradition in the macroeconomic literature. 15 This method has also been used by policymakers as a means to communicate policy objectives to the general public (Evans, 2011). One outstanding characteristic of the Equation (7) is that it includes interest rate smoothing as one of the objectives.…”
Section: Conventional Monetary Policy Rule ("Taylor Rule")mentioning
confidence: 99%
“…The method of approximating the expected utility of households through the weighted average of the variances of selected variables has a long tradition in the macroeconomic literature. 15 This method has also been used by policymakers as a means to communicate policy objectives to the general public (Evans, 2011). One outstanding characteristic of the Equation (7) is that it includes interest rate smoothing as one of the objectives.…”
Section: Conventional Monetary Policy Rule ("Taylor Rule")mentioning
confidence: 99%
“…Dueker et al (2007), Fernandez-Villaverde and Rubio-Ramirez (2007), Canova (2009), Liu et al (2011), Vavra (2008), Dew-Backer (2014), Meier and Sprengler (2015), Seoane (2016), Castelnuovo and Pellegrino (2018), among others, have shown that the parameters of dynamic stochastic general equilibrium (DSGE) models are not time invariant and that variations are small but persistent. Parameter variations do not necessarily imply that DSGE models are not structural (see, e.g., Cogley and Yagihashi, 2010, Chang et al, 2013, Schmitt-Grohe and Uribe, 2003, Hansen and Sargent, 2010, and Cogley et al, 2015, but they create concerns about the economic interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%
“…This approach provides intuition on a plethora of phenomena, and is the basis of the most elaborate computational Dynamic Stochastic General Equilibrium (DSGE) models that are used in practice for policy analysis [3]. Yet, its conceptual [4] and practical [5] shortcomings have been repeatedly pointed out.…”
Section: Introductionmentioning
confidence: 99%